PENGARUH MOTIVASI BERRESTASI TERHADAP PRESTASI KERJA KARYAWAN PANGERAN BEACH HOTEL PADANG - Adriani, Genia; Silfeni, Silfeni; Suyuthie, Hijriyantomi (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
This research starts from observations of researcher towards motivation work achievement against an accomplished the employee Pangeran Beach Hotel Padang alleged lack of employee accomplishments Pangeran Beach Hotel Padang. This research consists of 4 indicators of motivation overachievers: considering the risks, pay attention to feedback, creative/innovative, and resolution time, and consists of 6 indicators work achievement: accomplishments, honesty, discipline, cooperation, personality, and responsibility. Therefore the aim of this research is to know the motivational contribution towards employee achievements accomplished Pangeran Beach Hotel Padang. The results showed that: (1) Motivation Overachievers is at category enough (82,26%), (2) Achievement of work are at a sufficient category (64.52%), (3) test results of simple linear regression hypotheses obtained Fhitung 18,477 with sig. 0.00. This means significantly 0.00 0.05 Motivational variables then < Overachievers (X) may explain the variables work achievement (Y) significantly. So the variable affects variables achievers motivation work achievement. Furthermore with the R square of 0.235 variable influence Motivation means Doing (X) against the variable work achievement (Y) is 23.5%, while 76.5% are influenced by other factors such as: attitudes, knowledge, and education.Keywords : Work Motivation, achievement